The erosion of deterrence by director's liability insurance and the demand for stronger accountability through the Companies Act and other legal frameworks - Krawitz, David Eli (My University, 2016)
A company’s directors hold the highest position of decision making authority and have the responsibility to discharge their duties as prescribed under company law in the best interests of the company’s stakeholders. Any failure to discharge their duties responsibly can result in legal action being brought against them. Directors’ liability is intended to deter any wrongdoing on their part. However, the law permits companies to purchase a form of liability insurance called directors’ and officers’ (D&O) liability insurance to shield directors from exposure to liability. This study interrogates two research problems. Firstly, the study investigates the potential for D&O liability insurance to erode the deterrence function of directors’ liability in South Africa. Secondly, the study assesses the extent to which the Companies Act of 2008, the Constitution, other pieces of legislation and voluntary codes preserve the deterrence function intended by directors’ liability. Semi-structured interviews with the primary market participants in the local D&O insurance market were used to gain an in-depth understanding of how the D&O insurance market functioned in South Africa. The study’s findings revealed scarce preservation of the deterrence function of directors’ liability by local insurers. With respect to the second research problem, the study uncovered an acute awareness of the intent of the Companies Act to demand greater accountability from directors and to pierce the corporate veil. Consensus among respondents in the study confirmed that the South African directors’ and officers’ liability landscape is expected to shift over the next few years with the emergence of case law and increasing D&O claims.
MBA
Keywords: Directors of corporations -- Law and legislation -- South Africa. Corporate governance -- South Africa.Liability (Law) -- South Africa.Corporation law -- South Africa.